Long-term treatment of deep-vein thrombosis with low-molecular-weight heparin: An update of the evidence - Hull, Russell D.; Townshend, Grace (Thrombosis and Haemostasis, 2013)
This article reviews updated evidence-based knowledge on long-term treatment of deep-vein thrombosis (DVT) with low-molecular-weight heparin (LMWH) or vitamin K antagonists (VKAs). Eleven trials were identified comparing the two treatments in a broad spectrum of patients with DVT and with >100 study participants. Four comparative trials were identified in patients with cancer and DVT (in whom anticoagulation treatment is more complex and bleeding complications more frequent). In the 11 trials in broad patient populations, LMWHs were as effective as VKAs in preventing recurrent venous thromboembolism (VTE), and there were no consistent differences in the incidence of bleeding complications during long-term treatment. In patients with cancer, VTE recurrence was significantly reduced with LMWH versus VKA in two studies, while major bleeding complications did not differ between groups in any of the four trials. Current evidence-based European and American guidelines recommend LMWH over VKA for the long-term treatment of DVT in patients with cancer. LMWH and VKA are recommended over the new oral anticoagulant drugs, for which there are limited data on use in long-term treatment. Post-thrombotic syndrome (PTS), a common complication of DVT, causes considerable morbidity. Long-term use of tinzaparin reduced the risk of PTS compared with VKA in one trial, and a meta-analysis of nine studies in total demonstrated a consistently favourable effect of LMWHs versus VKA on PTS-related outcomes. Given the limited treatment options available for PTS, this suggests that LMWHs provide a useful therapeutic option in any patient particularly at risk of developing PTS.
Keywords: Deep-vein thrombosis; low-molecular-weight heparin; tinzaparin; post-thrombotic syndrome